Comparative Effectiveness of Gua Sha, Cryostretch, and Positional Release Technique on Tenderness and Function in Subjects with Plantar Fasciitis: a Randomized Clinical Trial - Baburao Jadhav, Aditi; Gurudut, Peeyoosha (International Journal of Therapeutic Massage & Bodywork, 2023)
Background: Plantar fasciitis (PF) can be treated effectively with manual techniques like cryostretch (CS) and the positional release technique (PRT). Although Gua Sha (GS) has been suggested in the literature for PF, its efficacy has not been studied in the research. Objective: To determine and compare the effectiveness of GS, CS, and PRT in subjects with PF in terms of pain intensity, pain pressure threshold, and foot function. Methods/Design: Thirty-six patients with PF (n=36) were randomly allocated to three study groups (12 in each group)—group GS, group CS, and group PRT, respectively. Settings: A randomized clinical trial was conducted at physiotherapy OPD in a tertiary health center. Participants: Subjects of all genders with plantar fasciitis of the age group 20-60 years. Thirty-six subjects with plantar fasciitis out of whom 12 were males and 24 females. There were no dropouts in this study. Intervention: The interventions included the Gua Sha technique (1 session), the cryostretch technique with a frozen tennis ball (3 sessions), and the positional release technique (7 sessions), along with common exercises for all three groups. Outcome Measures: Pain intensity, foot functions, and pain pressure threshold were assessed using the Numerical Pain Rating Scale, Foot Function Index, and pressure algometer, respectively, on day 1 (pre-intervention) and day 7 (post-intervention). Results: Between group analyses showed that group GS was more effective than CS and PRT for pain (p=.0001), group CS was more effective than GS and PRT for foot function (p=.0001) whereas group PRT was more effective than GS and CS for pain pressure threshold (p=.0001). Conclusion: Although all three groups showed improvement, Gua Sha was superior in terms of reducing pain, cryostretch for improving foot functions, and PRT for reducing tenderness. The interventions used in this study are cost-effective and have proved to be simple and safe techniques.